Single-molecule manipulation and detection by WGM-coupled photonic nanojets - Heng Li; Zhiyong Gong; Tong He; Tianli Wu; Yuchao Li; Yao Zhang (Discover Nano)
Abstract Optical manipulation and detection of single molecules, such as biomolecules and bacterial viruses, are crucial in single-molecule mechanics and biosensing. The interaction between light and individual molecules is weak due to the size of biomolecules (≤ 10 nm) being significantly smaller than the wavelength (λ) of light. This limitation results in a reduced optical gradient force and diminished detection sensitivity of light on biomolecules. To overcome this challenge, we propose a single-molecule trapping and sensing method that utilizes whisper-gallery mode (WGM) coupled photonic nanojets (PNJs). Our theoretical analysis demonstrates that a focused beam with a waist radius of λ/6 can be generated by WGM-coupled PNJs. By harnessing this sub-diffraction-limit focused beam, we create a stable nano-optical potential well for DNA molecules. The stiffness of the potential well is measured at 0.04 pN/nm/W, which is four orders of magnitude greater than that of conventional optical tweezers. Furthermore, the molecular configuration and refractive index of an individual DNA molecule can be detected by analyzing the shift in the WGM resonance peak and the intensity variation of the backscattering signal. This work provides theoretical guidance for the trapping and sensing of single molecules in the fields of chemistry, biology, and materials science.